Application of ultrasonic disintegration of post-coagulation sludge - Płonka, Izabela; Adamkowska, Monika (Instal, 2024)
Disintegration of sludge is a process consisting of the destruction of sludge flake structure, followed by rupture of the cell membrane and lysis of the microbial cells. Disintegration processes constitute a rapidly growing technology that is gaining more and more interest. The disintegration process results, inter alia, in the breaking of strong chemical bonds, therefore, it can be effective in the case of post-coagulation sludge. For this type of sludge, the expected effect is to improve its filtration properties. The integrated action between microorganisms and the cells alone, results in the release of the organic matter and biological water from inside of the cell. The process of sludge disintegration can be carried out using the following techniques: mechanical, thermal, chemical, or biological. The choice of a disintegration method is not simple because its effects are dependent on many parameters. One of those methods is ultrasonic application. Ultrasonic can negatively affect living organisms. It directly affects walls and membranes’ cells, leading to their deformation, perforation, or cell death. During the studies the following sludge parameters were determined: capillary suction time (CST), total solids (TS), volatile solids (VS), hydration and COD of supernatant liquid. After the disintegration process, it was observed that the value of TS increased from 0.04 % to 0.06% in the case of the longest exposure time of the sludge to the ultrasonic waves. It was also observed that the longer the process time and higher amplitude, the higher the COD value of the liquid. However, the capillary suction time decreased from 53 s for the non-disintegrated sludge to 25 s for the sludge subjected to ultrasonication – 50% amplitude and 10 minutes. This demonstrates the improvement of the filtration properties of sludge after disintegration.
Keywords: ultrasonic disintegration; post-coagulation sludge; sludge from water treatment plant